Positive electrode active material, positive electrode, and rechargeable lithium battery
By coating yttrium or aluminum on the surface of the positive electrode active substance of lithium cobalt oxide and layered lithium nickel manganese composite oxide, the problem of insufficient cobalt reserves and high cost of lithium cobalt oxide at high voltage is solved, and the problem of lithium cobalt oxide is achieved. High capacity, high density and long cycle life performance while reducing cobalt costs.
Patent Information
- Application Number
- CN202411056212.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-03
- Filing Date
- 2024-08-02
- Publication Date
- 2025-02-14
AI Technical Summary
The existing lithium cobalt oxide positive electrode active substances show insufficient cobalt reserves and high cost at high voltages, and their alternative materials such as lithium nickel manganese composite oxides have structural stability and cycles when achieving high voltage characteristics. The problem of insufficient lifespan.
Positive electrode active substances including lithium cobalt oxides and layered lithium nickel manganese composite oxides are used, and coatings such as yttrium or aluminum are coated on the surface to improve high voltage characteristics and cycle life while reducing cobalt costs.
The performance of high capacity, high density and long cycle life at high voltages is achieved, while reducing cobalt costs and improving the structural stability and high voltage characteristics of positive electrode active substances.
Smart Images

Figure CN119447218A_ABST
Abstract
Description
Technical Field
[0001] The present application discloses a positive electrode active material, a positive electrode, and a rechargeable lithium battery including the positive electrode. Background Art
[0002] Portable information devices such as cellular phones, laptop computers, and smart phones use rechargeable lithium batteries that have high energy density and are easy to carry. In addition, research has been actively conducted on using rechargeable lithium batteries with high energy density as a driving power source or power storage for hybrid or electric vehicles.
[0003] Various positive electrode active materials have been studied to realize rechargeable lithium batteries for such applications. Among them, lithium nickel-based oxides, lithium nickel-manganese-cobalt-based composite oxides, lithium nickel-cobalt-aluminum-based composite oxides, and lithium cobalt-based oxides can be used as positive electrode active materials.
[0004] Lithium cobalt oxides can achieve high density in the positive electrode and exhibit high voltage characteristics, but have problems associated with insufficient cobalt reserves and high prices. Accordingly, attempts have been made to replace lithium cobalt oxides with lithium nickel oxides or lithium manganese oxides, etc., using elements other than cobalt or mixtures of such elements. However, some of these positive electrode active materials have problems associated with achieving low average voltages and exhibit poor high voltage characteristics. Summary of the invention
[0005] Some embodiments provide positive electrode active materials that reduce the costs associated with positive electrode active materials including lithium cobalt-based oxides, but are capable of operating at high voltages and achieving high capacity, high density, and long cycle life.
[0006] In some embodiments, the positive electrode active material includes particles of a first positive electrode active material including a lithium cobalt-based oxide and particles of a second positive electrode active material in the form of single particles including a layered lithium nickel manganese-based composite oxide, the layered lithium nickel manganese-based composite oxide having a nickel content greater than or equal to about 60 mol% based on 100 mol% of the total metal content excluding lithium in the second positive electrode active material, wherein the first positive electrode active material and / or the second positive electrode active material includes a coating containing yttrium.
[0007] In some embodiments, the positive electrode includes: a positive electrode current collector, and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the positive electrode active material described above.
[0008] In some embodiments, a rechargeable lithium battery includes a positive electrode, a negative electrode, and an electrolyte.
[0009] The positive electrode active material according to some embodiments can reduce the price increase due to the use of lithium cobalt-based oxides, improve high voltage characteristics, and achieve high capacity, high density, and long cycle life characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 to Figure 4 is a cross-sectional view schematically illustrating a rechargeable lithium battery according to some embodiments.
[0011] Figure 5 : is a scanning electron microscope (SEM) image of the first positive electrode active material of Preparation Example 1.
[0012] Figure 6 This is a SEM image of the second positive electrode active material of Preparation Example 5.
[0013] Figure 7 This is the SEM image of the LCO small particles of Preparation Example 7.
[0014] <Description of Reference Numerals>
[0015] 100: Rechargeable lithium battery 10: Positive electrode
[0016] 11: Positive electrode lead lug 12: Positive electrode terminal
[0017] 20: Negative electrode 21: Negative electrode lead lug
[0018] 22: Negative electrode terminal 30: Separator
[0019] 40: electrode assembly 50: shell
[0020] 60: Sealing member 70: Electrode terminal piece
[0021] 71: Positive electrode terminal tab 72: Negative electrode terminal tab DETAILED DESCRIPTION
[0022] Hereinafter, specific embodiments will be described in detail so that those skilled in the art can easily implement them. However, the present disclosure may be embodied in many different forms and is not to be construed as limited to the example embodiments set forth herein.
[0023] The terms used herein are only used to describe the embodiments and are not intended to limit the present invention.Singular expressions such as "a", "an" and "the" include plural expressions unless the context clearly dictates otherwise.
[0024] As used herein, "combinations thereof" may be mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of the components.
[0025] In this document, it should be understood that terms such as “comprising,” “including,” or “having” are intended to indicate the presence of embodied features, quantities, steps, elements, or combinations thereof, but do not exclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or combinations thereof.
[0026] In the drawings, the thickness of layers, films, panels, regions, etc., are exaggerated for clarity, and the same reference numerals denote the same elements throughout the specification. It will be understood that when an element (such as a layer, film, region, or substrate) is referred to as being "on" another element, it can be directly on the other element, or intervening elements may also be present. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements.
[0027] In addition, the “layer” herein includes not only a shape formed on the entire surface when viewed from a plan view but also a shape formed on a partial surface.
[0028] In addition, the average particle size can be measured by methods well known to those skilled in the art, for example, it can be measured by a particle size analyzer or can be measured by a transmission electron microscope image or a scanning electron microscope image. Alternatively, the average particle size value can be obtained by using a dynamic light scattering method, performing data analysis, counting the number of particles in each particle size range, and calculating therefrom. Unless otherwise specified, the average particle size (D 50 ) may refer to the diameter of particles having a cumulative volume of 50% by volume in a particle size distribution. As used herein, when no definition is otherwise provided, the average particle size (D 50 ) means the diameter of a particle having a cumulative volume of 50 volume % in a particle size distribution obtained by randomly measuring the size (diameter or length of the major axis) of about 20 particles in a scanning electron microscope image.
[0029] In this document, "or" is not interpreted as an exclusive meaning. For example, "A or B" is interpreted to include A, B, and A+B, etc.
[0030] The term "metal" includes common metals, transition metals and metalloids (semimetals).
[0031] As used herein, a composition is "based on" a set of recited ingredients if the composition includes each of the recited ingredients. For example, a "lithium cobalt-based oxide" is an oxide that includes lithium and cobalt. Similarly, an "alcohol-based solvent" is a solvent that includes an alcohol.
[0032] As used herein, "single particle form" is a form of particulate matter in which at least 90% of the particles are single crystals without grain boundaries. In some embodiments, particles in single particle form may be aggregated with, for example, less than 10 individual particles attached to each other. In some embodiments, particles in single particle form are not aggregated. "Single particle form" includes particles that can be characterized as one particle, a monolithic structure, a unitary structure, a single grain, or non-aggregated particles, in which the particles are not aggregated with each other, but exist as independent phases (e.g., as single crystals) in terms of morphology.
[0033] Positive electrode active material
[0034] In some embodiments, the positive electrode active material includes particles of a first positive electrode active material including a lithium cobalt oxide, and particles of a second positive electrode active material including a layered lithium nickel manganese composite oxide, the layered lithium nickel manganese composite oxide having a nickel content greater than or equal to about 60 mol% based on 100 mol% of the total metal content excluding lithium in the second positive electrode active material, wherein at least one of the first positive electrode active material and the second positive electrode active material includes a coating containing yttrium. In some embodiments, the second positive electrode active material is in the form of a single particle. The coating is disposed on the surface of the particles of the first positive electrode active material or on the surface of the particles of the second positive electrode active material. The yttrium coating may be present only on the first positive electrode active material, only on the second positive electrode active material, or on both the first positive electrode active material and the second positive electrode active material.
[0035] Lithium cobalt oxides have excellent high voltage characteristics due to their material properties and excellent density characteristics due to their particulate form, so they are widely used in some batteries. However, as the cost of rare metal cobalt soars sharply, the manufacturing cost of lithium cobalt oxide positive electrode active materials will increase, and countermeasures need to be taken. Attempts have been made to use high nickel positive electrode active materials prepared by reducing the cobalt content, for example, lithium nickel cobalt manganese composite oxides or lithium nickel cobalt aluminum composite oxides, which have disadvantages such as lower drivable average voltage and poor high voltage characteristics than lithium cobalt oxides. Cobalt-free positive electrode active materials that do not use cobalt have been proposed, wherein positive electrode active materials having an olivine crystal structure (such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP), lithium manganese iron phosphate (LMFP), etc.) or a spinel crystal structure (such as lithium manganese oxide (LMO), etc.) have some limitations in achieving high capacity due to the small amount of available lithium in the structure. Lithium nickel manganese-based positive electrode active materials with a layered structure can have excellent capacity and efficiency characteristics due to the large amount of available lithium in the structure, and can be suitable for high-capacity batteries. However, since cobalt, which plays a key role in the layered structure, is removed from it, there is a problem of deteriorated structural stability or poor high-voltage characteristics.
[0036] In some embodiments, the yttrium coating is applied to the first positive electrode active material and / or the second positive electrode active material. For example, the yttrium coating can be applied while mixing a first positive electrode active material containing a lithium cobalt oxide and a second positive electrode active material containing a lithium nickel manganese composite oxide to provide a positive electrode active material with improved high voltage characteristics (e.g., initial discharge capacity and cycle life characteristics at high voltage), and reduce cobalt costs.
[0037] According to some embodiments, the second positive electrode active material is a particulate material including a layer containing nickel and manganese, so that it can have a shape similar to that of a lithium cobalt oxide. When mixed with the first positive electrode active material, the second positive electrode active material can achieve a very high positive electrode density and excellent high voltage characteristics. According to some embodiments of the positive electrode active material, compared with the case of mixing large particles and small particles made of lithium cobalt oxide, by including cobalt in a smaller content, not only high price competitiveness can be achieved, but also a positive electrode density at a level similar to that of lithium cobalt oxide can be achieved, and as a result, the capacity characteristics and cycle life characteristics at high voltage can be improved. In addition, in some embodiments, an yttrium coating can be introduced into the first positive electrode active material and / or the second positive electrode active material to increase structural stability and inhibit side reactions with the electrolyte, thereby improving high voltage characteristics.
[0038] The average particle size (D 50 ) may be larger than the average particle size (D 50 ). In this case, the first positive electrode active material may be expressed as a large particle or LCO large particle, and the second positive electrode active material may be expressed as a small particle, NM small particle, or NM single particle small particle. LCO means lithium cobalt oxide, and NM means lithium nickel manganese composite oxide. Because the first positive electrode active material includes lithium cobalt oxide and generally has a single particle form, the particles of the first positive electrode active material may be expressed as a single particle.
[0039] Average particle size (D 50 ) means the diameter of particles accounting for 50% by volume of the cumulative volume in a particle size distribution obtained by randomly measuring the sizes (diameters or lengths of major axes) of about 20 particles in a scanning electron microscope image.
[0040] The average particle size (D 50 ) may be, for example, about 10 μm to about 20 μm, about 10 μm to about 18 μm, or about 12 μm to about 16 μm. The average particle size (D 50) may be, for example, about 0.5 μm to about 8 μm, about 1 μm to about 7 μm, about 1.5 μm to about 6 μm, or about 2 μm to about 5 μm. When the average particle size of each positive electrode active material satisfies the above range, high capacity and high energy density can be achieved.
[0041] Based on a total of 100 wt % of the first positive electrode active material and the second positive electrode active material, the first positive electrode active material may be included in the positive electrode active material in an amount of about 60 wt % to about 95 wt %, for example, about 70 wt % to about 90 wt %. Based on a total of 100 wt % of the first positive electrode active material and the second positive electrode active material, the second positive electrode active material may be included in the positive electrode active material in an amount of about 5 wt % to about 40 wt %, for example, about 10 wt % to about 30 wt %. When the mixing ratio of the first positive electrode active material and the second positive electrode active material satisfies the above range, the energy density can be increased while maximizing the capacity.
[0042] First positive electrode active material
[0043] For example, the lithium cobalt-based oxide of the first positive electrode active material may be represented by Chemical Formula 1.
[0044] [Chemical formula 1]
[0045] Li a1 Co x1 M 1 1-x1 O2
[0046] In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤1, and M 1 It is one or more elements selected from Al, B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W and Zr.
[0047] In Chemical Formula 1, 0.9≤a1≤1.5, 0.9≤a1≤1.2, or 0.95≤a1≤1.1. In addition, x1 may be 0.7≤x1≤1, 0.8≤x1≤1, 0.9≤x1≤1, or 0.95≤x1<1.
[0048] As an example, the lithium cobalt-based oxide of the first positive electrode active material may further include aluminum. Aluminum may be a dopant, and in Chemical Formula 1, M 1 Al may be included. When aluminum is doped into the lithium cobalt-based oxide, capacity characteristics at high voltage and cycle life characteristics may be improved.
[0049] Based on 100 mol % of the total metal content excluding lithium in the lithium cobalt oxide, the aluminum content in the lithium cobalt oxide may be about 1 mol % to about 3 mol %, for example, about 1.5 mol % to about 2.5 mol %. When the content of the aluminum dopant satisfies the above range, the high voltage characteristics of the first positive electrode active material can be further improved.
[0050] The first positive electrode active material may include particles including lithium cobalt oxide and a coating disposed on the surface of the particles and including yttrium, aluminum, or a combination thereof. When the coating is formed on the first positive electrode active material, the cycle life characteristics or capacity characteristics at high voltage may be further improved.
[0051] When yttrium is included in the coating, the yttrium content in the coating may be about 0.01 mol% to about 1 mol%, for example, about 0.01 mol% to about 0.9 mol%, about 0.01 mol% to about 0.7 mol%, about 0.01 mol% to about 0.5 mol%, about 0.01 mol% to about 0.3 mol% or about 0.05 mol% to about 0.1 mol%, based on 100 mol% of the total metal content excluding lithium in the first positive electrode active material. The yttrium content in the coating can be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the amount of yttrium coating on the first positive electrode active material satisfies the above range, high voltage characteristics can be improved while minimizing capacity degradation.
[0052] When aluminum is included in the coating, the aluminum content in the coating may be about 0.1 mol% to about 2 mol%, for example, about 0.1 mol% to about 1.5 mol%, about 0.1 mol% to about 1 mol%, about 0.1 mol% to about 0.8 mol%, or about 0.2 mol% to about 0.5 mol%, based on 100 mol% of the total metal content excluding lithium in the first positive electrode active material. When the amount of aluminum coating on the first positive electrode active material satisfies the above range, high voltage characteristics can be improved while minimizing capacity degradation.
[0053] The thickness of the coating of the first positive electrode active material may be about 5nm to about 500nm, for example, about 30nm to about 500nm, about 30nm to about 450nm, about 30nm to about 400nm, about 30nm to about 350nm, about 30nm to about 300nm, about 30nm to about 250nm, about 30nm to about 200nm, about 30nm to about 150nm, about 50nm to about 500nm, about 80nm to about 500nm or about 100nm to about 500nm. When the coating meets this thickness range, the structural stability of the positive electrode active material can be improved without increasing resistance or reducing capacity due to coating, and side reactions with the electrolyte can be effectively suppressed. The thickness of the coating can be measured by, for example, SEM, TEM, TOF-SIMS, XPS or EDS analysis, for example, by TEM-EDS line profile.
[0054] For example, the coating may include both yttrium and aluminum. For example, in the coating, the yttrium may be present in the form of islands, and the aluminum may be present in the form of a continuous film.
[0055] Second positive electrode active material
[0056] Based on 100mol% of the total metal content excluding lithium in the lithium nickel manganese composite oxide, the layered lithium nickel manganese composite oxide of the second positive electrode active material may have a nickel content greater than or equal to about 60mol%, for example, about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. If the nickel content meets the above range, even if the cobalt content is reduced, high capacity can be achieved and structural stability can be increased.
[0057] For example, based on 100 mol% of the total metal content excluding lithium in the lithium nickel manganese composite oxide, the manganese content of the second positive electrode active material may be greater than or equal to about 15 mol%, for example, about 15 mol% to about 40 mol%, about 15 mol% to about 35 mol%, about 15 mol% to about 30 mol%, or about 20 mol% to about 30 mol%. If the manganese content satisfies the above range, the positive electrode active material can improve structural stability while achieving high capacity.
[0058] The layered lithium nickel manganese composite oxide may be a lithium nickel manganese aluminum composite oxide further including aluminum in addition to nickel and manganese. Inclusion of aluminum in the composite oxide may be advantageous for maintaining a stable layered structure even when cobalt is excluded from the structure. Based on the total metal content excluding lithium in the layered lithium nickel manganese aluminum composite oxide at 100 mol%, the aluminum content may be greater than or equal to about 0.1 mol%, greater than or equal to about 0.5 mol%, or greater than or equal to about 1 mol%, for example, about 1 mol% to about 3 mol%, about 1 mol% to about 2.5 mol%, about 1 mol% to about 2 mol%, or about 1 mol% to about 1.9 mol%. If the aluminum content satisfies the above range, a stable layered structure can be maintained even when cobalt is excluded, structural collapse due to charging and discharging can be suppressed, and long cycle life characteristics of the positive electrode active material can be achieved.
[0059] For example, the layered lithium nickel manganese composite oxide may be represented by Chemical Formula 2.
[0060] [Chemical Formula 2]
[0061] Li a2 Ni x2 Mn y2 Al z2 M 2 w2 O 2-b2 X b2
[0062] In Chemical Formula 2, 0.9 ≤ a2 ≤ 1.8, 0.6 ≤ x2 ≤ 0.8, 0.1 ≤ y2 ≤ 0.4, 0 ≤ z2 ≤ 0.03, 0 ≤ w2 ≤ 0.3, 0.9 ≤ x2 + y2 + z2 + w2 ≤ 1.1, and 0 ≤ b2 ≤ 0.1, M 2 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, and Zr, and X is one or more elements selected from F, P, and S.
[0063] In Chemical Formula 2, 0.9 ≤ a2 ≤ 1.5 or 0.9 ≤ a2 ≤ 1.2. Additionally, Chemical Formula 2 may include aluminum, in which case it may satisfy 0.6 ≤ x2 ≤ 0.8, 0.1 ≤ y2 ≤ 0.39, 0.01 ≤ z2 ≤ 0.03, and 0 ≤ w2 ≤ 0.29, for example, 0.6 ≤ x2 ≤ 0.8, 0.1 ≤ y2 ≤ 0.39, 0.01 < z2 ≤ 0.03, and 0 ≤ w2 ≤ 0.29.
[0064] In Chemical Formula 2, for example, 0.6 ≤ x2 ≤ 0.79, 0.6 ≤ x2 ≤ 0.78, 0.6 ≤ x2 ≤ 0.75, 0.65 ≤ x2 ≤ 0.8 or 0.7 ≤ x2 ≤ 0.79; 0.1 ≤ y2 ≤ 0.35, 0.1 ≤ y2 ≤ 0.30, 0.1 ≤ y2 ≤ 0.29, 0.15 ≤ y2 ≤ 0.39 or 0.2 ≤ y2 ≤ 0.3; 0.01 ≤ z2 ≤ 0.025, 0.01 < z2 ≤ 0.02 or 0.01 < z2 ≤ 0.019; and 0 ≤ w2 ≤ 0.28, 0 ≤ w2 ≤ 0.27, 0 ≤ w2 ≤ 0.26, 0 ≤ w2 ≤ 0.25, 0 ≤ w2 ≤ 0.24, 0 ≤ w2 ≤ 0.23, 0 ≤ w2 ≤ 0.22, 0 ≤ w2 ≤ 0.21, 0 ≤ w2 ≤ 0.2, 0 ≤ w2 ≤ 0.15, 0 ≤ w2 ≤ 0.1 or 0 ≤ w2 ≤ 0.09.
[0065] The layered lithium nickel manganese composite oxide may be a cobalt-free compound that does not include cobalt or includes a very small amount of cobalt. For example, in the layered lithium nickel manganese composite oxide, based on the total metal content excluding lithium in 100 mol% of the layered lithium nickel manganese composite oxide, the cobalt content may be about 0 mol% to about 0.01 mol% or about 0 mol% to about 0.001 mol%. By applying a second positive electrode active material that does not include cobalt or includes a very small amount of cobalt, the preparation cost can be reduced, and according to some embodiments, poor high-voltage characteristics can be effectively prevented.
[0066] The second positive electrode active material may be in the form of single particles. For example, the particles may each be a single crystal substantially free of grain boundaries. In some embodiments, the particles in the form of single particles may aggregate with, for example, fewer than 10 single particles attached to each other. In some embodiments, the particles in the form of single particles do not aggregate.
[0067] The second positive electrode active material may include a coating provided on the surface of the single particle and containing yttrium, aluminum, or a combination thereof. As an example, the second positive electrode active material includes a coating containing yttrium, and the coating may optionally further include aluminum.
[0068] Based on 100 mol% of the total metal content excluding lithium in the second positive electrode active material, the yttrium content in the coating of the second positive electrode active material may be about 0.01 mol% to about 1 mol%, for example, about 0.01 mol% to about 0.9 mol%, about 0.01 mol% to about 0.7 mol%, about 0.01 mol% to about 0.5 mol%, about 0.01 mol% to about 0.3 mol% or about 0.05 mol% to about 0.1 mol%. The yttrium content in the coating can be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. If the amount of yttrium coating on the second positive electrode active material satisfies the above range, high voltage characteristics can be improved while minimizing capacity degradation.
[0069] If aluminum is included in the coating of the second positive electrode active material, the aluminum content may be about 0.1 mol% to about 2 mol%, for example, about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.8 mol% to about 1.3 mol%, based on 100 mol% of the total metal content excluding lithium in the second positive electrode active material. This refers only to the content of aluminum included in the coating, which is different from the aluminum included in the particles. The aluminum content in the coating can be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. If the aluminum content in the coating satisfies this range, the coating can have a uniform and thin thickness, which may not increase the resistance of the positive electrode active material, and effectively inhibit side reactions with the electrolyte, thereby improving the cycle life characteristics of the rechargeable lithium battery under high voltage and high temperature conditions.
[0070] The coating of the second positive electrode active material may be in the form of a film that continuously surrounds the surface of a single particle, or, for example, may be in the form of a shell that surrounds the entire surface of a single particle. This is different from a structure that only partially coats a portion of the surface of the particle. The coating according to some embodiments may be formed to have a very thin and uniform thickness, and completely cover the surface of a single particle, which neither increases the resistance of the positive electrode active material nor degrades the capacity, but rather exhibits improved structural stability, and can effectively inhibit side reactions with the electrolyte, resulting in a long cycle life characteristic at high voltage.
[0071] The thickness of the coating of the second positive electrode active material may be about 5nm to about 500nm, for example, about 30nm to about 500nm, about 30nm to about 450nm, about 30nm to about 400nm, about 30nm to about 350nm, about 30nm to about 300nm, about 30nm to about 250nm, about 30nm to about 200nm, about 30nm to about 150nm, about 50nm to about 500nm, about 80nm to about 500nm or about 100nm to about 500nm. If the coating meets this thickness range, the structural stability of the positive electrode active material can be improved, for example, the resistance will not be increased or the capacity will be reduced due to coating, and the side reaction with the electrolyte can be effectively suppressed. The thickness of the coating can be measured by, for example, SEM, TEM, TOF-SIMS, XPS or EDS analysis, for example, by TEM-EDS line profile.
[0072] In the coating layer of the second positive electrode active material, yttrium may be present in the form of islands, and aluminum may be present in the form of a continuous film.
[0073] For example, aluminum and yttrium can be mixed in one coating. Alternatively, aluminum and yttrium can form separate layers. For example, the second positive electrode active material may include a first coating disposed on the surface of a single particle and comprising aluminum, and a second coating disposed on the first coating and comprising yttrium. The first coating in the form of a thin film can be formed when aluminum is first attached or adsorbed to the surface of a single particle, and then yttrium can be applied thereon to form a second coating. Of course, aluminum and yttrium can be mixed in the first coating and the second coating, but the first coating can be an aluminum-rich coating composed mainly of aluminum, and the second coating can be a yttrium-rich coating composed mainly of yttrium. In this case, yttrium can be present in the second coating in the form of islands, but there is no particular limitation.
[0074] The thickness of the first coating and the second coating is not particularly limited. However, the thickness of the first coating may be about 10nm to about 200nm, for example, about 20nm to about 200nm, about 30nm to about 200nm, or about 30nm to about 180nm. The thickness of the second coating may be about 20nm to about 300nm, for example, about 20nm to about 250nm, about 20nm to about 200nm, about 30nm to about 300nm, or about 50nm to about 300nm. If each thickness meets the above range, the structural stability of the positive electrode active material can be improved without increasing resistance or reducing capacity due to coating, and the cycle life characteristics at high voltage can be improved by effectively suppressing the side reaction with the electrolyte.
[0075] Method for preparing positive electrode active material
[0076] In some embodiments, the method of preparing a positive electrode active material includes: preparing a first positive electrode active material in the form of particles including a lithium cobalt oxide; preparing a second positive electrode active material in the form of a single particle including a layered lithium nickel manganese composite oxide, the layered lithium nickel manganese composite oxide having a nickel content greater than or equal to about 60 mol% based on 100 mol% of the total metal content excluding lithium in the second positive electrode active material; and mixing the first positive electrode active material and the second positive electrode active material. The first positive electrode active material preparation process or the second positive electrode active material preparation process may include a process of coating with yttrium. The aforementioned positive electrode active material can be prepared by the above method.
[0077] As an example, the method for preparing the positive electrode active material is a first positive electrode active material coating process, in which a yttrium raw material, an aluminum raw material or a combination thereof is added to an aqueous solvent and mixed, and a lithium cobalt-based oxide is added thereto and mixed, followed by drying and a first heat treatment.
[0078] The yttrium raw material may include, for example, yttrium nitrate, yttrium sulfate, yttrium carbonate, yttrium hydroxide, or a combination thereof. The aluminum raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof. The aqueous solvent may include distilled water, an alcohol solvent, or a combination thereof.
[0079] When yttrium coating is performed, the yttrium content in the yttrium raw material can be designed to be about 0.01 mol% to about 1 mol%, for example, about 0.01 mol% to about 0.9 mol%, about 0.01 mol% to about 0.7 mol%, about 0.01 mol% to about 0.5 mol%, about 0.01 mol% to about 0.3 mol% or about 0.05 mol% to about 0.1 mol%, based on 100 mol% of the total metal content excluding lithium in the first positive electrode active material. If the amount of yttrium coating on the first positive electrode active material satisfies the above range, high voltage characteristics can be improved while minimizing capacity degradation.
[0080] When aluminum coating is performed, the aluminum content in the aluminum raw material can be designed to be about 0.1 mol% to about 2 mol%, for example, about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol% or about 0.8 mol% to about 1.3 mol%, based on 100 mol% of the total metal content excluding lithium in the first positive electrode active material.
[0081] The first heat treatment may form a coating on the surface of the lithium cobalt oxide particles, for example, in an oxygen atmosphere at a temperature range of about 700° C. to about 950° C., about 750° C. to about 950° C., or about 800° C. to about 950° C. for about 2 to about 20 hours or about 3 to about 10 hours.
[0082] As an example, the method for preparing the positive electrode active material is a second positive electrode active material coating process, in which an yttrium raw material, an aluminum raw material or a combination thereof is added to an aqueous solvent and mixed, and a layered lithium nickel manganese composite oxide in the form of a single particle is added thereto and mixed, followed by drying and performing a second heat treatment.
[0083] Lithium nickel manganese composite oxides have a significantly different residual lithium content and different surface characteristics from oxides of other compositions (e.g., conventional nickel oxides such as lithium nickel cobalt manganese composite oxides or lithium nickel cobalt aluminum composite oxides, etc.), and conventional coating methods may not be able to successfully form a good coating in the form of a uniform film thereon. In some embodiments, the following method is applied to improve high voltage characteristics: a coating having a very thin thickness is uniformly formed on the surface of a layered lithium nickel manganese composite oxide having a very small amount of cobalt and a nickel content of greater than or equal to about 60 mol%.
[0084] The yttrium raw material may include, for example, yttrium nitrate, yttrium sulfate, yttrium carbonate, yttrium hydroxide or a combination thereof. The aluminum raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide or a combination thereof. For example, the aluminum raw material may include aluminum sulfate, and in this case, it is advantageous to form a coating having a uniform thickness on the surface of the lithium nickel manganese composite oxide particles. The aqueous solvent may include distilled water, an alcohol solvent or a combination thereof.
[0085] When yttrium coating is performed, the yttrium content in the yttrium raw material may be about 0.01 mol% to about 1 mol%, for example, about 0.01 mol% to about 0.9 mol%, about 0.01 mol% to about 0.7 mol%, about 0.01 mol% to about 0.5 mol%, about 0.01 mol% to about 0.3 mol% or about 0.05 mol% to about 0.1 mol%, based on 100 mol% of the total metal content excluding lithium in the second positive electrode active material. If the amount of yttrium coating on the second positive electrode active material satisfies the above range, high voltage characteristics can be improved while minimizing capacity degradation.
[0086] When aluminum coating is performed, the aluminum content in the aluminum raw material may be about 0.1 mol% to about 2 mol%, for example, about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.8 mol% to about 1.3 mol%, based on 100 mol% of the total metal content excluding lithium in the second positive electrode active material. If the content of the coating raw material is designed to have this range, the coating layer can be formed to have a thin and uniform thickness of tens or hundreds of nanometers, which can reduce the amount of generated gas under high voltage conditions of the rechargeable lithium battery and improve high capacity and long cycle life characteristics.
[0087] The solution obtained by mixing the yttrium raw material, the aluminum raw material or a combination thereof in an aqueous solvent may have a pH of about 1.5 to about 3.5 (e.g., about 2.0 to about 3.4, about 2.5 to about 3.3, about 2.7 to about 3.3, or about 2.9 to about 3.2). The layered lithium nickel manganese composite oxide in the form of a single particle may be mixed with the solution for, for example, about 5 minutes to about 80 minutes, about 5 minutes to about 60 minutes, or about 5 minutes to about 40 minutes. After stirring, the mixed solution may have a pH of about 4.5 to about 8.5 (e.g., about 5.0 to about 8.0, about 5.5 to about 7.5, or about 6.0 to about 7.0). In some embodiments, these conditions provide a coating with uniform thickness.
[0088] The second heat treatment may be performed in an oxygen atmosphere at, for example, about 700° C. to about 850° C., about 750° C. to about 840° C., or about 800° C. to about 830° C. for about 2 hours to about 20 hours, or about 3 hours to about 10 hours.
[0089] The first positive electrode active material and the second positive electrode active material may be mixed at a weight ratio of about 60:40 to about 95:5, for example, about 70:30 to about 90: 10. In some embodiments, the capacity and cycle life characteristics may be improved while maximizing the energy density by mixing the electrode active materials at this ratio.
[0090] Positive electrode
[0091] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material. In addition to the aforementioned positive electrode active material, the positive electrode active material layer may further include other types of positive electrode active materials. In addition, the positive electrode active material layer may optionally further include a binder, a conductive material, or a combination thereof.
[0092] According to some embodiments, the loading level of the positive electrode active material layer may be about 10 mg / cm 2 ~ about 40mg / cm 2 , for example, about 10 mg / cm 2 ~about 30mg / cm 2 or about 10 mg / cm 2 ~about 20mg / cm 2. In addition, the density of the positive electrode active material layer in the final compressed positive electrode may be about 3.5 g / cc to about 3.7 g / cc, for example, about 3.5 g / cc to about 3.6 g / cc or about 3.5 g / cc to about 3.58 g / cc. When the positive electrode active material according to some embodiments is applied, it may be advantageous to achieve such a loading level and positive electrode density, and a positive electrode satisfying the loading level and positive electrode density within the above range is suitable for realizing a high-capacity, high-energy-density rechargeable lithium battery.
[0093] Binder
[0094] The binder improves the bonding properties of the positive electrode active material particles to each other and to the positive electrode current collector. Examples of the binder may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, and nylon, but are not limited thereto.
[0095] Conductive Materials
[0096] A conductive material may be included to provide electrode conductivity, and any conductive material may be used as the conductive material unless it causes a chemical change. Examples of the conductive material may include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0097] The binder and the conductive material may each independently be about 0.5 wt % to about 5 wt % or about 0.5 wt % to about 3 wt % based on 100 wt % of the positive electrode active material layer.
[0098] The positive electrode current collector may include Al foil, but is not limited thereto.
[0099] Rechargeable lithium battery
[0100] Some embodiments provide a rechargeable lithium battery including the aforementioned positive electrode, a negative electrode, and an electrolyte.
[0101] Depending on the shape, the rechargeable lithium battery may be cylindrical, prismatic, pouch-type, coin-type, etc. Figure 1 to Figure 4 A schematic diagram for explaining a rechargeable lithium battery according to an embodiment. Figure 1 A cylindrical battery is shown, Figure 2 A prismatic cell is shown, and Figure 3 and Figure 4 Pouch cell shown. Figure 1 to Figure 4 , the rechargeable lithium battery 100 includes an electrode assembly 40 having a separator 30 interposed between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is accommodated. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte (not shown). Figure 1 As shown in , the rechargeable lithium battery 100 may include a sealing member 60 that seals the housing 50. Figure 2 In the embodiment, the rechargeable lithium battery 100 may include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. Figure 3 and Figure 4 As shown in , the rechargeable lithium battery 100 may include electrode tabs 70, that is, a positive electrode tab 71 and a negative electrode tab 72, which serve as an electrical path for guiding current formed in the electrode assembly 40 to the outside.
[0102] The rechargeable lithium battery according to some embodiments may be rechargeable at a high voltage, or may be suitable for driving at a high voltage. For example, the charging voltage of the rechargeable lithium battery may be greater than or equal to about 4.45V, about 4.45V to about 4.7V, about 4.45V to about 4.6V, or about 4.45V to about 4.55V. By applying the positive electrode active material according to some embodiments, the rechargeable lithium battery can also significantly reduce the amount of gas generated when charging even at a high voltage, and can achieve high capacity and long cycle life characteristics.
[0103] Negative electrode
[0104] The negative electrode may include a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector, and the negative electrode active material layer may include a negative electrode active material, a binder, a conductive material, or a combination thereof.
[0105] Negative electrode active material
[0106] The negative electrode active material may include a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, or a transition metal oxide.
[0107] The material that reversibly intercalates / deintercalates lithium ions may include, for example, crystalline carbon, amorphous carbon, or a combination thereof as a carbonaceous negative electrode active material. The crystalline carbon may be irregular or flaky, sheet-like, spherical, or fibrous natural graphite or artificial graphite. The amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonization product, calcined coke, etc.
[0108] The lithium metal alloy includes an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.
[0109] The material capable of doping / dedoping lithium can be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material can include silicon, silicon-carbon composite, SiO x (0 < x < 2), Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, such as Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof) or a combination thereof. The Sn-based negative electrode active material can be Sn, SnO2, Sn alloy, or a combination thereof.
[0110] The silicon-carbon composite can be a composite of silicon and amorphous carbon. The average particle size (D 50 ) can be, for example, about 0.5 μm to about 20 μm. According to some embodiments, the silicon-carbon composite can be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, it can include secondary particles (cores) in which silicon primary particles are aggregated and an amorphous carbon coating (shell) on the surface of the secondary particles. Amorphous carbon can also be present between the silicon primary particles. For example, the silicon primary particles can be coated with amorphous carbon. The secondary particles can be dispersed in the amorphous carbon matrix.
[0111] The silicon-carbon composite can further include crystalline carbon. For example, the silicon-carbon composite can include a core containing crystalline carbon and silicon particles and an amorphous carbon coating on the surface of the core. The crystalline carbon can be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon can include soft carbon or hard carbon, mesophase pitch carbonized product, and calcined coke.
[0112] When the silicon-carbon composite includes silicon and amorphous carbon, based on 100% by weight of the silicon-carbon composite, the content of silicon can be about 10% by weight to about 50% by weight, and the content of amorphous carbon can be about 50% by weight to about 90% by weight. Additionally, when the composite includes silicon, amorphous carbon, and crystalline carbon, based on 100% by weight of the silicon-carbon composite, the content of silicon can be about 10% by weight to about 50% by weight, the content of crystalline carbon can be about 10% by weight to about 70% by weight, and the content of amorphous carbon can be about 20% by weight to about 40% by weight.
[0113] In addition, the thickness of the amorphous carbon coating may be about 5 nm to about 100 nm. The average particle diameter (D 50 ) of the silicon particles (primary particles) may be about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles may exist alone as silicon, in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon may be represented by SiO x (0 < x < 2). At this time, the atomic content ratio of Si:O indicating the degree of oxidation may be about 99:1 to about 33:67. As used herein, when no other definition is provided, the average particle diameter (D 50 ) indicates the diameter of the particles in which the cumulative volume is about 50% by volume in the particle distribution.
[0114] The Si-based negative electrode active material or the Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. When the Si-based negative electrode active material or the Sn-based negative electrode active material is mixed and used with the carbon-based negative electrode active material, the mixing ratio may be a weight ratio of about 1:99 to about 90:10.
[0115] Binder
[0116] The binder is used to bond the negative electrode active material particles to each other and is also used to bond the negative electrode active material to the current collector. The binder may be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.
[0117] The non-aqueous binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.
[0118] The aqueous binder may include styrene-butadiene rubber, (meth)acrylate esterified styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, epichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene-propylene-diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenol resin, epoxy resin, polyvinyl alcohol, or a combination thereof.
[0119] When the aqueous binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. As the cellulose-based compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, and their alkali metal salts may be mixed and used. The alkali metal may be Na, K, or Li.
[0120] The dry binder may be a polymer material that can be turned into fibers, and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.
[0121] Conductive Materials
[0122] A conductive material may be included to provide electrode conductivity, and any conductive material may be used as the conductive material unless it causes a chemical change. Examples of the conductive material include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powder or metal fiber of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0123] Based on 100 wt % of the negative electrode active material layer, the content of the negative electrode active material may be about 95 wt % to about 99.5 wt %, and based on 100 wt % of the negative electrode active material layer, the content of the binder may be about 0.5 wt % to about 5 wt %. For example, the negative electrode active material layer may include about 90 wt % to about 99 wt % of the negative electrode active material, about 0.5 wt % to about 5 wt % of the binder, and about 0.5 wt % to about 5 wt % of the conductive material.
[0124] current collector
[0125] The negative electrode current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) or an alloy thereof, and may be in the form of foil, sheet or foam. The thickness of the negative electrode current collector may be, for example, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 7 μm to about 10 μm.
[0126] Electrolyte
[0127] The electrolyte for a rechargeable lithium battery may include, for example, a nonaqueous organic solvent and a lithium salt.
[0128] The non-aqueous organic solvent is used as a medium for transporting ions participating in the electrochemical reaction of the battery. The non-aqueous organic solvent may be a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent, an alcohol solvent, an aprotic solvent, or a combination thereof.
[0129] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, valerolactone, caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. In addition, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles (such as R-CN, where R is C2~C 20 Straight chain, branched chain or cyclic hydrocarbon group, which includes a double bond, an aromatic ring or an ether group, etc.); amide (such as dimethylformamide); dioxolane (such as 1,3-dioxolane, 1,4-dioxolane, etc.); cyclopentane, etc.
[0130] The nonaqueous organic solvent may be used alone or in a mixture of two or more types, and when two or more types are used in a mixture, the mixing ratio may be appropriately adjusted according to desired battery performance, as is well known to those skilled in the art.
[0131] When a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate may be mixed and used, and the cyclic carbonate and the chain carbonate may be mixed in a volume ratio of about 1:1 to about 1:9.
[0132] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, a carbonate-based solvent and an aromatic hydrocarbon organic solvent may be mixed and used in a volume ratio of about 1:1 to about 30:1.
[0133] The electrolyte may further include ethyl vinyl carbonate, vinylene carbonate or ethylene carbonate-based compounds to improve the battery cycle life.
[0134] Examples of the ethylene carbonate-based compound may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0135] The lithium salt dissolved in the non-aqueous organic solvent supplies lithium ions in the battery, enables the basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts may include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are integers of 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB) and lithium bis(oxalato)borate (LiBOB).
[0136] The concentration of the lithium salt may be in the range of about 0.1 M to about 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate ion conductivity and viscosity, so that excellent performance can be achieved and lithium ions can be efficiently transferred.
[0137] Diaphragm
[0138] Depending on the type of rechargeable lithium battery, there may be a separator between the positive electrode and the negative electrode. The separator may include polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer film of two or more layers thereof, and a mixed multilayer film (such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.).
[0139] The separator may include a porous substrate and a coating including an organic material, an inorganic material, or a combination thereof on one or both surfaces of the porous substrate.
[0140] The porous substrate can be a polymer film formed by any one selected from the group consisting of polymer polyolefins (such as polyethylene and polypropylene), polyesters (such as polyethylene terephthalate and polybutylene terephthalate), polyacetals, polyamides, polyimides, polycarbonates, polyetherketones, polyaryletherketones, polyetheretherketones, polyetherimides, polyamideimides, polybenzimidazoles, polyethersulfones, polyphenylene oxides, cyclic olefin copolymers, polyphenylene sulfides, polyethylene naphthalate, glass fibers, TEFLON, and polytetrafluoroethylene, or a polymer film formed by a copolymer or a mixture of two or more thereof.
[0141] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.
[0142] The organic material may include a (meth)acryl-based copolymer including a first structural unit derived from (meth)acrylamide, and a second structural unit including at least one of a structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acrylamide sulfonic acid or a salt thereof.
[0143] The inorganic material may include inorganic particles selected from the group consisting of Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof, but is not limited thereto. The average particle size (D 50 ) may be from about 1 nm to about 2000 nm, for example, from about 100 nm to about 1000 nm or from about 100 nm to about 700 nm.
[0144] An organic material and an inorganic material may be mixed in one coating layer, or a coating layer including an organic material and a coating layer including an inorganic material may be stacked.
[0145] The coating layer may have a thickness of about 0.5 μm to about 20 μm, for example, about 1 μm to about 10 μm or about 1 μm to about 5 μm.
[0146] Some additional non-limiting embodiments include:
[0147] A1. The positive electrode active material of embodiment "A", which includes: particles of a first positive electrode active material including a lithium cobalt-based oxide, and particles of a second positive electrode active material, optionally in the form of single particles, including a layered lithium nickel manganese-based composite oxide, the layered lithium nickel manganese-based composite oxide having a nickel content greater than or equal to about 60 mol% based on 100 mol% of the total metal content excluding lithium in the second positive electrode active material, wherein the first positive electrode active material and / or the second positive electrode active material includes a coating containing yttrium.
[0148] A2. The positive electrode active material of embodiment A1, wherein the average particle size (D 50 ) is larger than the average particle size (D 50 ).
[0149] A3. The positive electrode active material of embodiment A1, wherein the average particle size (D 50) is in the range of about 10 μm to about 20 μm, and the average particle size (D 50 ) is in the range of about 0.5 μm to about 8 μm.
[0150] A4. The positive electrode active material of embodiment A1, wherein the first positive electrode active material is about 60 wt % to about 95 wt % of the positive electrode active material, and the second positive electrode active material is about 5 wt % to about 40 wt % of the positive electrode active material.
[0151] A5. The positive electrode active material of embodiment A1, wherein the lithium cobalt-based oxide of the first positive electrode active material is represented by Chemical Formula 1:
[0152] [Chemical formula 1]
[0153] Li a1 Co x1 M 1 1-x1 O2
[0154] Wherein, in chemical formula 1, 0.9≤a1≤1.8, 0.6≤x1≤1, and M 1 It is one or more elements selected from Al, B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W and Zr.
[0155] A6. The positive electrode active material of embodiment A1, wherein the lithium cobalt oxide of the first positive electrode active material further includes aluminum, and the aluminum content in the lithium cobalt oxide is about 1 mol% to about 3 mol% based on 100 mol% of the total metal content excluding lithium in the lithium cobalt oxide.
[0156] A7. The positive electrode active material of embodiment A1, wherein particles of the first positive electrode active material include a lithium cobalt-based oxide, and a coating disposed on a surface of the particle, the coating comprising yttrium, aluminum, or a combination of yttrium and aluminum.
[0157] A8. The positive electrode active material of embodiment A7, wherein the coating contains yttrium, and the yttrium content in the coating is in the range of about 0.01 mol % to about 1 mol % based on 100 mol % of the total metal content excluding lithium in the first positive electrode active material.
[0158] A9. The positive electrode active material of embodiment A7, wherein the coating contains aluminum, and the aluminum content in the coating is in the range of about 0.1 mol % to about 2 mol % based on 100 mol % of the total metal content excluding lithium in the first positive electrode active material.
[0159] A10. The positive electrode active material of embodiment A7, wherein the coating layer of the first positive electrode active material has a thickness in a range of about 5 nm to about 500 nm.
[0160] A11. A positive electrode active material of implementation A1, wherein in the layered lithium nickel manganese composite oxide of the second positive electrode active material, based on 100 mol% of the total metal content excluding lithium in the layered lithium nickel manganese composite oxide, the nickel content in the layered lithium nickel manganese composite oxide is in the range of about 60 mol% to about 80 mol%, and the manganese content in the layered lithium nickel manganese composite oxide is greater than or equal to about 15 mol%.
[0161] A12. A positive electrode active material of implementation A1, wherein the layered lithium nickel manganese composite oxide of the second positive electrode active material further includes aluminum, and the aluminum content in the layered lithium nickel manganese composite oxide is in the range of about 1 mol% to about 3 mol% based on 100 mol% of the total metal content excluding lithium in the layered lithium nickel manganese composite oxide.
[0162] A13. A positive electrode active material of implementation A1, wherein in the layered lithium nickel manganese composite oxide of the second positive electrode active material, based on 100 mol % of the total metal content excluding lithium in the layered lithium nickel manganese composite oxide, the cobalt content in the layered lithium nickel manganese composite oxide is in the range of about 0 mol % to about 0.01 mol %.
[0163] A14. The positive electrode active material of embodiment A1, wherein the layered lithium nickel manganese composite oxide of the second positive electrode active material is represented by Chemical Formula 2:
[0164] [Chemical formula 2]
[0165] Li a2 Ni x2 Mn y2 Al z2 M 2 w2 O 2-b2 X b2
[0166] Wherein, in Chemical Formula 2, 0.9≤a2≤1.8, 0.6≤x2≤0.8, 0.1≤y2≤0.4, 0≤z2≤0.03, 0≤w2≤0.3, 0.9≤x2+y2+z2+w2≤1.1 and 0≤b2≤0.1, M 2 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W and Zr, and X is one or more elements selected from F, P and S.
[0167] A15. The positive electrode active material of embodiment A1, wherein the second positive electrode active material comprises a coating disposed on the individual particles and comprising yttrium, aluminum, or a combination thereof.
[0168] A16. The positive electrode active material of embodiment A15, wherein the coating contains yttrium, and the yttrium content in the coating is in the range of about 0.01 mol % to about 1 mol % based on 100 mol % of the total metal content excluding lithium in the second positive electrode active material.
[0169] A17. The positive electrode active material of embodiment A15, wherein the coating comprises aluminum, and the aluminum content in the coating is in the range of about 0.1 mol % to about 2 mol % based on 100 mol % of the total metal content excluding lithium in the second positive electrode active material.
[0170] A18. The positive electrode active material of embodiment A15, wherein the coating of the second positive electrode active material has a thickness of about 5 nm to about 500 nm.
[0171] A19. The positive electrode active material of embodiment A15, wherein the coating layer of the second positive electrode active material comprises yttrium and aluminum, and in the coating layer, the yttrium is present in the form of islands and the aluminum is present in the form of a continuous film.
[0172] A20. The positive electrode active material of embodiment A15, wherein the second positive electrode active material includes a first coating layer on the surface of the single particle and comprising aluminum, and a second coating layer disposed on the first coating layer and comprising yttrium.
[0173] A21. A positive electrode comprising a positive electrode current collector, and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material of Embodiment A1.
[0174] A22. The positive electrode of embodiment A21, wherein
[0175] The positive electrode active material layer has a density of about 3.5 g / cc to about 3.7 g / cc.
[0176] A23. A rechargeable lithium battery comprising the positive electrode of embodiment A21, a negative electrode and an electrolyte.
[0177] A24. The rechargeable lithium battery of embodiment A23, wherein the charging voltage is greater than or equal to about 4.45V.
[0178] The following describes embodiments and comparative examples of the present disclosure. However, the embodiments described below are merely examples of the present disclosure, and the present disclosure is not limited to the embodiments described below.
[0179] Preparation Example 1: Preparation of the first positive electrode active material (LCO large particles)
[0180] Prepare a first composite oxide having LiCo 0.985 Al 0.015 O2 composition and an average particle size of about 18 μm (D 50 ). Alumina is added to the first composite oxide, and then mixed for 20 minutes to 60 minutes. In this article, based on 100 mol% of the total metal content excluding lithium in the final first positive electrode active material, the alumina is designed to have an aluminum content of 0.4 mol%. The mixture is then heat-treated at 950° C. for 8 hours to prepare a first positive electrode active material. Figure 5 A scanning electron microscope image of the first positive electrode active material is shown.
[0181] Preparation Example 2: Preparation of the first positive electrode active material (LCO large particles)
[0182] The first composite oxide is added together with water and yttrium nitrate to coat yttrium on the first composite oxide. The product is then dried. The dried product is mixed with Al2O3 and then heat treated at 950°C for 8 hours to prepare a first positive electrode active material. In this article, the yttrium content in yttrium nitrate is designed to be 0.05 mol%, based on 100 mol% of the total metal content excluding lithium in the final first positive electrode active material, and the aluminum oxide is designed to have an aluminum content of 0.4 mol%, based on 100 mol% of the total metal content excluding lithium in the final first positive electrode active material.
[0183] Preparation Example 3: Preparation of the first positive electrode active material (LCO large particles)
[0184] LiCo 0.985 Al 0.015 The first composite oxide of O2 was used as the first positive electrode active material without Al and Y coating.
[0185] Table 1 briefly shows the design of Preparation Examples 1 to 3. Table 1 also shows the capacity and cycle life measured by the method of Evaluation Example 1 after the positive electrode active materials according to Preparation Examples 1 to 3 were respectively applied in substantially the same manner as in Example 1 described later to manufacture positive electrodes and rechargeable lithium battery cells.
[0186] (Table 1)
[0187]
[0188] Preparation Example 4: Preparation of the Second Positive Electrode Active Material (NM Small Particles)
[0189] Ni 0.75 Mn 0.25(OH)2, LiOH and Al2O3 were mixed in a molar ratio of 1:1:0.02, and then heat-treated at 850°C for 8 hours in an oxygen atmosphere to prepare a second composite oxide in the form of single particles having LiNi 0.75 Mn 0.23 Al 0.02 O2 composition and an average particle size of about 3 μm (D 50 ).
[0190] After aluminum sulfate and yttrium nitrate are mixed with a distilled water solvent, a second composite oxide is added thereto and then mixed for 20 to 60 minutes. In this article, based on 100 mol% of the total metal content excluding lithium in the final second positive electrode active material, aluminum sulfate is designed to have an aluminum content of 0.4 mol%, and yttrium nitrate is designed to have a yttrium content of 0.05 mol%. After removing the solvent from the solution and drying at 190 ° C, heat treatment is performed at 825 ° C for 8 hours in an oxygen atmosphere to prepare a second positive electrode active material.
[0191] Preparation Example 5: Preparation of the Second Positive Electrode Active Material (NM Small Particles)
[0192] A second positive electrode active material was prepared in substantially the same manner as in Preparation Example 4, except that the yttrium content of yttrium nitrate was designed to be 0.1 mol %. Figure 6 A scanning electron microscope image of the second positive electrode active material according to Preparation Example 5 is shown.
[0193] Preparation Example 6: Preparation of the Second Positive Electrode Active Material (NM Small Particles)
[0194] A second positive electrode active material was prepared in substantially the same manner as in Preparation Example 4, except that Al coating alone was performed without adding yttrium nitrate.
[0195] Table 2 briefly shows the design of Preparation Examples 4 to 6. Table 2 also shows the capacity and cycle life measured in substantially the same manner as in Evaluation Example 1 after manufacturing a positive electrode and a rechargeable lithium battery cell by applying each of the positive electrode active materials of Preparation Examples 4 to 6 in substantially the same manner as in Example 1.
[0196] (Table 2)
[0197]
[0198] Preparation Example 7: Preparation of the Second Positive Electrode Active Material (LCO Small Particles)
[0199] After aluminum sulfate was mixed with distilled water solvent, a molten-salt-soluble solid having an average particle size (D 50 ) 0.98 Al 0.02O2 particles, then, mixed for 20 minutes to 60 minutes. In this article, based on 100mol% of the total metal content excluding lithium in the final second positive electrode active material, the aluminum content in aluminum sulfate is designed to be 0.4mol%. The solvent is removed from the mixed solution, dried at 190°C, and heated at 825°C for 8 hours to obtain the second positive electrode active material according to Preparation Example 7. Figure 7 A scanning electron microscope image of the second positive electrode active material (LCO small particles) according to Preparation Example 7 is shown.
[0200] Preparation Example 8: Preparation of the Second Positive Electrode Active Material (LCO Small Particles)
[0201] The second positive electrode active material was prepared in substantially the same manner as in Preparation Example 7, except that Al and Y were coated by adding yttrium nitrate together with aluminum sulfate. Herein, the content of yttrium in yttrium nitrate was designed to be 0.05 mol%, based on 100 mol% of the total metal content excluding lithium in the final second positive electrode active material.
[0202] In Table 3, the designs of Preparation Examples 7 and 8 are briefly shown. Table 3 also shows the capacity and cycle life measured in substantially the same method as in Evaluation Example 1 after manufacturing a positive electrode and a rechargeable lithium battery cell by applying each of the positive electrode active materials of Preparation Examples 7 to 8 in substantially the same manner as in Example 1.
[0203] (Table 3)
[0204]
[0205] Example 1
[0206] 1. Fabrication of positive electrode
[0207] The first positive electrode active material (LCO large particles) of Preparation Example 1 and the second positive electrode active material (NM small particles) of Preparation Example 4 were mixed at a weight ratio of 8:2 to prepare a positive electrode active material according to Example 1.
[0208] 98.5wt% of the positive electrode active material, 1.0wt% of the polyvinylidene fluoride binder and 0.5wt% of the carbon nanotube conductive material were mixed to prepare a positive electrode active material layer slurry, and the slurry was coated on an aluminum foil current collector, then dried and compressed to make a positive electrode. The density of the final compressed positive electrode was about 3.52g / cc.
[0209] 2. Manufacturing of rechargeable lithium battery cells
[0210] 97.5 wt% of graphite negative electrode active material, 1.5 wt% of carboxymethyl cellulose and 1 wt% of styrene butadiene rubber were mixed in an aqueous solvent to prepare a negative electrode active material layer slurry. The negative electrode active material layer slurry was coated on a copper foil current collector, and then dried and compressed to manufacture a negative electrode.
[0211] A rechargeable lithium battery cell was manufactured in a common method using a polytetrafluoroethylene separator and using an electrolyte prepared by dissolving 1M LiPF6 in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7.
[0212] Comparative Example 1
[0213] A positive electrode active material, a positive electrode, and a rechargeable lithium battery cell were manufactured in substantially the same manner as in Example 1, except that the first positive electrode active material (LCO large particles) of Preparation Example 1 and the second positive electrode active material (LCO small particles) of Preparation Example 7 were mixed in a weight ratio of 8:2 to prepare the positive electrode active material.
[0214] Evaluation Example 1: Evaluation of electrochemical characteristics and mixture density
[0215] As initial charge and discharge, the rechargeable lithium battery cells according to Example 1 and Comparative Example 1 were charged to 4.5V at a constant current of 0.2C and charged to 0.05C at a constant voltage, and discharged to a cut-off voltage of 3.0V at 0.2C at 25°C to measure the initial discharge capacity, and the results are shown in Table 4 as 4.5V capacity (mAh / g).
[0216] Subsequently, the battery cells were repeatedly charged at 1.0C and discharged at 1.0C in a voltage range of 3.0V to 4.5V at 45°C for 50 or more times to calculate the ratio of the 50th cycle discharge capacity to the initial discharge capacity, and the results are shown in Table 4 as 4.5V cycle life (%, @50cy).
[0217] In addition, each positive electrode density in the pressed state of Example 1 and Comparative Example 1 was measured, and the results are shown in Table 4 as positive electrode density (g / cc).
[0218] (Table 4)
[0219]
[0220] Referring to Table 4, Example 1 exhibits improved initial discharge capacity and high voltage cycle life characteristics compared to Comparative Example 1 while maintaining almost the same positive electrode density as Comparative Example 1.
[0221] While the present disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it is to be understood that the present disclosure is not limited to these embodiments, but is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the claims.
Claims
1. A positive electrode active material comprising: particles of a first positive electrode active material including a lithium cobalt-based oxide, and particles of a second positive electrode active material in the form of individual particles of a layered lithium nickel manganese-based composite oxide having a nickel content of greater than or equal to 60 mol % based on 100 mol % of the total metal content excluding lithium in the second positive electrode active material, The first positive electrode active material and / or the second positive electrode active material comprises a coating comprising yttrium.
2. The positive electrode active material according to claim 1, wherein An average particle size of the particles of the first positive electrode active material is larger than an average particle size of the individual particles of the second positive electrode active material.
3. The positive electrode active material according to claim 1, wherein The average particle size of the particles of the first positive electrode active material is in the range of 10 μm to 20 μm, and The average particle size of the single particles of the second positive electrode active material is in the range of 0.5 μm to 8 μm.
4. The positive electrode active material according to claim 1, wherein The first positive electrode active material is 60 wt % to 95 wt % of the positive electrode active material, and the second positive electrode active material is 5 wt % to 40 wt % of the positive electrode active material.
5. The positive electrode active material according to claim 1, wherein The lithium cobalt-based oxide of the first positive electrode active material is represented by Chemical Formula 1: [Chemical formula 1] Li a1 Yes x1 M 1 1-x1 O2 in, In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤1, and M 1 It is one or more elements selected from Al, B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W and Zr.
6. The positive electrode active material according to claim 1, wherein The lithium cobalt-based oxide of the first positive electrode active material further includes aluminum, and The aluminum content in the lithium cobalt-based oxide is 1 mol % to 3 mol % based on 100 mol % of the total metal content excluding lithium in the lithium cobalt-based oxide.
7. The positive electrode active material according to claim 1, wherein The particles of the first positive electrode active material include a lithium cobalt-based oxide, and a coating layer disposed on a surface of the particles, the coating layer containing yttrium, aluminum, or a combination of yttrium and aluminum.
8. The positive electrode active material according to claim 7, wherein The coating layer includes yttrium, and the yttrium content in the coating layer is in a range of 0.01 mol % to 1 mol % based on 100 mol % of the total metal content excluding lithium in the first positive electrode active material.
9. The positive electrode active material according to claim 7, wherein The coating layer includes aluminum, and the aluminum content in the coating layer is in a range of 0.1 mol % to 2 mol % based on 100 mol % of the total metal content excluding lithium in the first positive electrode active material.
10. The positive electrode active material according to claim 7, wherein The coating layer of the first positive electrode active material has a thickness in the range of 5 nm to 500 nm.
11. The positive electrode active material according to claim 1, wherein In the layered lithium nickel manganese composite oxide of the second positive electrode active material, based on 100 mol % of the total metal content excluding lithium in the layered lithium nickel manganese composite oxide, the nickel content in the layered lithium nickel manganese composite oxide is in the range of 60 mol % to 80 mol %, and the manganese content in the layered lithium nickel manganese composite oxide is greater than or equal to 15 mol %.
12. The positive electrode active material according to claim 1, wherein The layered lithium nickel manganese composite oxide of the second positive electrode active material further includes aluminum, and the aluminum content in the layered lithium nickel manganese composite oxide is in the range of 1 mol% to 3 mol% based on 100 mol% of the total metal content excluding lithium in the layered lithium nickel manganese composite oxide.
13. The positive electrode active material according to claim 1, wherein In the layered lithium nickel manganese composite oxide of the second positive electrode active material, the cobalt content in the layered lithium nickel manganese composite oxide is in the range of 0 mol % to 0.01 mol % based on 100 mol % of the total metal content excluding lithium in the layered lithium nickel manganese composite oxide.
14. The positive electrode active material according to claim 1, wherein The layered lithium nickel manganese composite oxide of the second positive electrode active material is represented by Chemical Formula 2: [Chemical formula 2] Li a2 Ni x2 Mr y2 Al z2 M 2 w2 O 2-b2 X b2 in, In chemical formula 2, 0.9≤a2≤1.8, 0.6≤x2≤0.8, 0.1≤y2≤0.4, 0≤z2≤0.03, 0≤w2≤0.3, 0.9≤x2+y2+z2+w2≤1.1, and 0≤b2≤0.1, M 2 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W and Zr, and X is one or more elements selected from F, P and S.
15. The positive electrode active material according to claim 1, wherein The second positive electrode active material includes a coating disposed on the individual particles and comprising yttrium, aluminum, or a combination thereof.
16. The positive electrode active material according to claim 15, wherein The coating layer includes yttrium, and the yttrium content in the coating layer is in a range of 0.01 mol % to 1 mol % based on 100 mol % of the total metal content excluding lithium in the second positive electrode active material.
17. The positive electrode active material according to claim 15, wherein The coating layer includes aluminum, and the aluminum content in the coating layer is in a range of 0.1 mol % to 2 mol % based on 100 mol % of the total metal content excluding lithium in the second positive electrode active material.
18. The positive electrode active material according to claim 15, wherein The coating layer of the second positive electrode active material has a thickness of 5 nm to 500 nm.
19. The positive electrode active material according to claim 15, wherein The coating layer of the second positive electrode active material contains yttrium and aluminum, and in the coating layer, yttrium exists in the form of islands, and aluminum exists in the form of a continuous film.
20. The positive electrode active material according to claim 15, wherein The second positive electrode active material includes a first coating layer disposed on a surface of the single particle and containing aluminum, and a second coating layer disposed on the first coating layer and containing yttrium.
21. A positive electrode comprising: a positive electrode current collector, and a positive electrode active material layer on the positive electrode current collector, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 20.
22. The positive electrode of claim 21, wherein The positive electrode active material layer has a density of 3.5 g / cc to 3.7 g / cc.
23. A rechargeable lithium battery comprising: The positive electrode according to claim 21 or 22, negative electrode, and Electrolyte.
24. The rechargeable lithium battery of claim 23, wherein The charging voltage of the rechargeable lithium battery is greater than or equal to 4.45V.